The intellectuality of al-Dihlawi: A review on his contribution in science of prophetic tradition - Nazri M.A.; Mustafa L.; Othman F.M.; Sakat A.A.; Usman A.H.; Amin M.F.M. (Mediterranean Center of Social and Educational Research, 2024)
Indexed by Scopus